2023
DOI: 10.3389/fbioe.2023.1182422
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of novel intra- and extramedullary assembly fixation for proximal humerus fractures in the elderly

Zhengguo Zhu,
Zuhao Chang,
Wei Zhang
et al.

Abstract: Purpose: A novel intra- and extramedullary assembly fixation method was introduced, which achieved good clinical results in complex proximal humeral fractures; however, evidence of its comparability with traditional fixation is lacking. This biomechanical study aimed to compare it with traditional fixation devices in osteoporotic proximal humeral fractures.Methods: Three-part proximal humeral fractures with osteopenia were created on 12 pairs of fresh frozen humerus specimens and allocated to three groups: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…By comparing with the results of Zhu et al (2023b) and Chang et al (2023) , the reliability and high fidelity of the finite element model in this study are confirmed. The results from FEA and biomechanical studies indicate that the LLP-IRPBC group exhibits greater structural stiffness compared to the LLP-IFS group.…”
Section: Discussionsupporting
confidence: 63%
“…By comparing with the results of Zhu et al (2023b) and Chang et al (2023) , the reliability and high fidelity of the finite element model in this study are confirmed. The results from FEA and biomechanical studies indicate that the LLP-IRPBC group exhibits greater structural stiffness compared to the LLP-IFS group.…”
Section: Discussionsupporting
confidence: 63%